The administration of the doctoral examination at South African higher education institutions - Schulze, S.; Lemmer, E.M. (South African Journal of Higher Education, 2019)
The doctorate is the apex of all qualifications in universities worldwide and in South Africa. The expected outcome of the doctorate is original research, presented as a thesis. The thesis should demonstrate a student’s ability to do high-level research and contribute meaningfully to a discipline. Thesis assessment is through the submission of written examiner reports by examiners external to the university. However, the literature indicates limitations in thesis examination. A qualitative study was undertaken at six South African universities to gather data from a purposeful sample of expert informants and relevant documents. Wenger and Lave’s (1991) Community of Practice theory informed the inquiry. The findings indicated challenges in appointing examiners; vague criteria for ancillary requirements to the thesis; and discrepancies in the quality of examiner reports and examiner recommendations, which delay graduation. Recommendations were made for a more transparent examination process and supervisor training in the examination process.